Important Factors in the Development of Young Entrepreneurial Groups in Forest Honeybee Cultivation and Products - Setiadi, Edi; Sulaiman, Adhi Iman; ., Chusmeru; Windiasih , Rili; Ahmadi, Dadi; Suyanto , Edy; Wijayanti, Irene Kartika Eka (Journal of Ecohumanism, 2024)
The younger generation emerges as a pivotal subject in perpetuating sustainable development, with an expectation to also play a role in rural areas to optimize the potential of local resources, thereby mitigating the negative impacts of urbanization and reducing labor migration. Thus, the research aims to analyze the crucial factors supporting the role of youth in the development of socio-economic institutions in rural areas. The study employs the Participatory Learning and Action method to construct community learning experiences through interviews, Focus Group Discussions, documentation analysis, and observation. The research informants consist of the Young Farmer Group "Prawita Garden", which has successfully cultivated forest honeybees and developed rural tourism destinations. Interactive research analysis is utilized for data reduction, verification, and triangulation, complemented by modeling using the Vensin application. The research findings indicate that the "Prawita Garden" young farmer group has emerged as a pioneer and inspirator in honeybee cultivation and production, particularly of unique honey types such as Klanceng Honeybee, imported European Honeybee, and local Honeybee. Crucial factors in the development of young farmer institutionalization include entrepreneurial motivation and group formation, local indigenous practices passed down through generations or integrated into traditions intertwined with the social capital prevalent in rural communities.